2022
DOI: 10.1186/s12935-022-02579-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value and biological function of LRRN4 in colorectal cancer

Abstract: Background Several nervous and nerve-related biomarkers have been detected in colorectal cancer (CRC) and can contribute to the progression of CRC. However, the role of leucine-rich repeat neuronal 4 (LRRN4), a recently identified neurogenic marker, in CRC remains unclear. Methods We examined the expression and clinical outcomes of LRRN4 in CRC from TCGA-COREAD mRNA-sequencing datasets and immunohistochemistry in a Chinese cohort. Furthermore, colo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For instance, Yuan et al [ 34 ] previously demonstrated that differential expression of INHBB significantly influences the prognosis of CRC patients and is associated with various oncogenic signaling pathways. Similarly, Xu et al [ 35 ] reported that LRRN4 modulates the malignant phenotype of CRC tumor cells through the rat sarcoma (RAS)/MAPK signaling pathway. Another study highlighted that overexpression of FSTL3 impacts CRC prognosis and can promote epithelial-to-mesenchymal transition (EMT) and aerobic glycolysis via the activated β-catenin pathway, thereby affecting CRC cell invasiveness and metastatic capability [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Yuan et al [ 34 ] previously demonstrated that differential expression of INHBB significantly influences the prognosis of CRC patients and is associated with various oncogenic signaling pathways. Similarly, Xu et al [ 35 ] reported that LRRN4 modulates the malignant phenotype of CRC tumor cells through the rat sarcoma (RAS)/MAPK signaling pathway. Another study highlighted that overexpression of FSTL3 impacts CRC prognosis and can promote epithelial-to-mesenchymal transition (EMT) and aerobic glycolysis via the activated β-catenin pathway, thereby affecting CRC cell invasiveness and metastatic capability [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the MAPK signaling pathway are strongly associated with the progression of colon cancer cells ( Burotto et al, 2014 ). Xu C et al demonstrated that altering the expression of ERK1/2 and Akt genes downstream of the MAPK signaling pathway regulates DNA synthesis, proliferation, and apoptosis in colon cancer cells ( Xu C. et al, 2022 ). Ma W et al downregulated the phosphorylated expression of MEK1/2, ERK1/2, and RAF1 in the MAPK signaling pathway as a way to regulate the malignant proliferating phenotype of colon tumors ( Ma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%